Glycemic disorders and coronary collateral circulation - Ivan Vasil'evich Starostin; K A Talitskiy; O S Bulkina; Yury Alexandrovich Karpov (Сахарный диабет)
Although collateral circulation is the essential means of perfusion for ischemized myocardium, its efficiency varies substantially within and between the species. There is both experimental and clinical evidence for association of glycemic disorders with inadequate col- lateral circulation. Current article reviews general mechanisms of collateral circulation failure due to such metabolic disturbances with regard for stages of arteriogenesis. We also highlight horizons of further studies in this field.